Kelimpahan Jenis Tanaman Pangan Pada Pekarangan Rumah Penduduk Di Desa Mandikapau Barat, Kecamatan Karang Intan, Kabupaten Banjar - Pujah Naciah; Anang Kadarsah; Krisdianto Krisdianto (Universitas Lambung Mangkurat, 2023)
The yard plays an important role in meeting the needs of the community, namely by planting in the yard of the house, especially to meet the needs of the household, especially in meeting the needs of the family's home food, can be planted with food crops such as fruit, vegetables, tubers, spices, etc. The aim of the research was to study the types of food plants found and to know the abundance index and dominance index of food plants found in Mandikapau Barat Village. The method of this research is to determine the area of the yard, take samples of the yard, identify the types of food plant categories (fruits, vegetables, tubers, and spices), and calculate the abundance index and dominance index of these food plants. Results Food plants found totaled 25 families 32 genera 40 species (27 fruits; 5 vegetables; 2 tubers; 6 spices). The highest relative abundance index of the three locations was in the category of spices, bulbs, fruits, vegetables with a value of (28%; 6%; 5%; 4%) with galangal, cassava, papaya and cayenne pepper plants. The average dominance index shows a value of 0.131 which is included in the low category.KEYWORDS: Mandikapau; Kabupaten Banjar; food plant; dominance index